Five years of an Alongside Midwifery Unit at a Swiss Perinatal Centre: a retrospective descriptive study (Swiss Medical Weekly, 2026)
BACKGROUND: Overmedicalisation during childbirth, especially in low-risk pregnancies, is an increasing issue. Alongside Midwifery Units (AMUs) are a midwife-led, low-intervention option that maintains access to hospital resources. However, in 2022, only 3.7% of births in Switzerland took place outside hospitals. The UK has emphasised educating women about their birth choices, notably through the “Birthplace in England” programme and NICE guidelines. Evidence shows that out-of-hospital births in low-risk pregnancies are safe for mother and child. This retrospective descriptive study analyses maternal and neonatal outcomes, transfer rates and indications for transfer over a 5-year period at the AMU of the Cantonal Hospital Aarau.METHODS: All women registering for delivery at the AMU between May 2017 and December 2022 were considered. Strict inclusion criteria ensured a low-risk cohort (singleton, cephalic presentation, 370/7 to 420/7 weeks, uncomplicated pregnancy). Exclusion criteria were pre-existing maternal or fetal disease, prior caesarean section and need for continuous maternal or fetal monitoring. Data were extracted from electronic medical records and included maternal characteristics, mode of delivery, transfer indications, and maternal and neonatal outcomes. Statistical analyses were primarily descriptive. Comparisons between women delivering at the AMU and those transferred to the maternity ward used Wilcoxon rank-sum and Fisher’s exact tests (α = 0.05, unadjusted). The study was approved by the regional ethics committee (BASEC-Nr. 2023-00745).RESULTS: Of 1196 women registered, 1034 were included in the analysis. Among 838 women who started labour at the AMU, 75% (n = 627) delivered there, while 25% (n = 211) were transferred peripartum, mainly due to failure to progress (53.1%) or analgesia request (34.6%). Most transferred women (74.8%) still had a vaginal birth. At 48.3% vs 17.7%, women who gave birth at the AMU were significantly more likely to have no birth injury. The postpartum transfer rate was 7.7%, primarily for retained placenta, perineal repair or uterine atony. Neonatal outcomes were favourable: 0.6% of AMU births had a 5-minute APGAR